Understanding the Effect of Fruits Maturity Level on Its Effectiveness as a Dielectric for Parallel Plate Capacitors for Senior High School Student - Yerika Puspa Rosanti; Raden Manzilah Mubarokah Fahra; Siti Nurul Khotimah (International Journal of STEM Education for Sustainability, 2025)
Indonesia is an agrarian country that produces fruits in abundant quantities and in various variations. Fruits contain diverse contents, one of which can be utilized as a dielectric capacitor. This research is conducted to provide senior high school students with an understanding of the influence of dielectrics from several fruits on capacitance. This experiment analyzed the maturity level of fruits and their effectiveness as dielectric capacitors for parallel plate capacitors. Due to the maturity level of fruits being composed of many variables, this study is focused on differences in water content, sugar concentration, and acidity level. Through laboratory experiments, researchers examined these factors in guava, papaya, pear, mango, and apple fruits. The capacitance value of parallel plates is measured using an LCR meter, and it is found that the capacitance of parallel plates with air dielectric increases significantly when infiltrated with fruit dielectric. Water content has a significant influence. The capacitance value is also high in fruits with high water content and vice versa. Meanwhile, the influence of sugar concentration is less significant in this study, only noticeable in papaya fruits. However, this is supported by the fruit's acidity level as seen from its pH value. Fruits with high pH values also have high capacitance. Experiments found that as fruits ripen, their water content, sugar concentration, and pH value tend to increase. This causes mature fruits to be more effective when used as dielectric capacitors.